Carput service / Nur Rasyidah Bilai - Bilai, Nur Rasyidah (2022)
The carput service mobile application launched on the 1st of September 2016 but our story began two years earlier at a small office space in Petaling Jaya.Carput was started by three friends who wanted Malaysians to get more reliable, transparent and quicker assistance when their car breaks down. We leverage on both technology and the human touch to be quick yet empathetic in achieving the highest standards of customer service. This company provide many service which flat tyre, tow truck, change car battery and emergency petrol delivery.